1970
DOI: 10.1203/00006450-197003000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Concentrations of Plasma Luteinizing Hormone in Infants, Children, and Adolescents with Normal and Abnormal Gonadal Function

Abstract: ExtractThis communication reports the development of a sensitive, reproducible, and specific radioimmunoassay for luteinizing hormone (LH) in plasma and the application of this method to a cross-sectional survey of plasma LH concentratior~s in 243 infants, children, and adolescents with normal and abnormal growth and sexual development. One nanogram of Hartree purified human pituitary LH standard was immunologically equivalent to 13.7 mIU of the Second International Reference Preparation of Human Menopausal Go… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
14
0

Year Published

1970
1970
1981
1981

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(16 citation statements)
references
References 22 publications
2
14
0
Order By: Relevance
“…Serums were also obtained from 93 normal females (ages 2-31 yr), 71 normal males (ages [5][6][7][8][9][10][11][12][13][14][15][16][17][18] yr), and 12 hypopituitary patients (ages 13-25 yr). The LH concentrations in some of these individuals were reported previously (1), as were the radioimmunoassay techniques for determining FSH and LH (2)(3)(4)(5)(6)(7)(8)(9).…”
Section: Methodsmentioning
confidence: 99%
“…Serums were also obtained from 93 normal females (ages 2-31 yr), 71 normal males (ages [5][6][7][8][9][10][11][12][13][14][15][16][17][18] yr), and 12 hypopituitary patients (ages 13-25 yr). The LH concentrations in some of these individuals were reported previously (1), as were the radioimmunoassay techniques for determining FSH and LH (2)(3)(4)(5)(6)(7)(8)(9).…”
Section: Methodsmentioning
confidence: 99%
“…Their data indicate that mean LH and FSH levels in serum show significant elevations 24 hr before ovulation. Previous studies [16,23,24,28] have shown the corand girls and their stage of sexual development. It has further been demonstrated that the rise in urinary excretion of FSH and LH, as measured by the techniques employed in this work, correlates favorably with the progressing stage of sexual development in males [2,25).…”
Section: Quantitative Comparisonsmentioning
confidence: 99%
“…In this regard, it is of interest to note the serum LH concentrations (13.5, 19.6 mIU/ml) of the two 15 yr old females in stage III (Table IV). Root, Moshang, Bongiovanni, and Eberlein have indicated that a 17 yr old female with idiopathic hypopituitarism who had a serum LH concentration of 13.7 mIU/ ml attained sexual maturity (13).…”
Section: Methodsmentioning
confidence: 99%